The sexual orientation wage gap: the role of occupational sorting, human capital, and discrimination - Heather Antecol; Anneke Jong; Michael D. Steinberger (Institute for the Study of Labor (IZA), 2007)
Using data from the 2000 U.S. Census, we document and explore three alternative explanations for the sexual orientation wage gap: occupational sorting, human capital differences, and discrimination. We find lesbian women earn more than their heterosexual counterparts irrespective of marital status while gay men earn less than their married heterosexual counterparts but more than their cohabitating heterosexual counterparts. Using a Oaxaca-Blinder decomposition we find that differences in human capital accumulation (particularly education) are the main reason behind the observed wage advantages, while discrimination and occupational sorting play a minimal role at best. Wage penalties, on the other hand, are largely explained by discrimination. Interestingly, while we do find there are some differences in the relative roles of our three alternative explanations across the wage distribution using a DiNardo, Fortin, Lemieux decomposition, the main conclusions from the Oaxaca-Blinder decomposition persist.
Keywords: 330; Lohndifferenzierung; Homosexualität; Beruf; Humankapital; Diskriminierung; USA